THE COMPARATIVE RELIABILITY EVALUATION FOR THREE CONFIGURATION OF THE FAULT-TOLERANT SYSTEM WITH MAJORITY STRUCTURE - Mandziy, B.A.; Volochyi, B.Y.; Ozirkovsky, L.D.; М.М. Zmysnyi; Muliak, O.V. (Radio Electronics, Computer Science, Control, 2013)
A comparision of reliability, which can provide the faulttolerant system with a majority structure, namely: three majority structure embedded in majority structure, majority structure with the reconfiguration of the core structure and majority structure with a fixed rule decision was performed in the paper. Designing of fault-tolerant systems implemented with the help of analytical modeling with representation them as discrete-continuous stochastic system. Results of the comparison showed that mean time to failure for fault-tolerant system based on majority structure with fixed rule decision such as «2 of 3» plus 6 technical systems in reserve by 28 % higher compared with the fault-tolerant system using three majority structures embedded in majority structure and by 7 % higher compared with the rate obtained for faulttolerant system with reconfiguration of core of majority structure type structure «3 of 5» plus 4 technical systems in reserve.